ConductAR: an augmented reality based tool for iterative design of conductive ink circuits - Narumi, Koya; Hodges, Steve; Kawahara, Yoshihiro (Proceedings of UbiComp 2015, 2015)
Recent advances in materials science have resulted in a range of commercially viable and easy-to-use conductive inks which novices, hobbyists, educators, students and researchers are now using to design and build interactive circuits quickly. Despite the ease with which practitioners can construct working circuits, one of the major limitations of designing circuits on-the-fly is the difficulty of detecting and understanding errors in prototype circuits. As well as short- and open-circuits, which often prevent a circuit from working at all, more subtle issues like high resistance traces can result in poor performance. Many users can't readily work out how to successfully modify their circuits, and they often don't have the tools or expertise to measure the relevant circuit parameters. In this paper we present ConductAR, a tool which can recognize and analyze hand-drawn, printed and hybrid conductive ink patterns. An on-screen augmented reality style interaction helps users to understand and enhance circuit operation. A key element of ConductAR is its ability to calculate the resistance of a circuit using a camera attached to an off-the-shelf PC or tablet. Our sparse coding technique is fast enough to support rapid iterative prototyping on real circuits using a conductive ink marker and/or eraser as shown in Figure 1. The system thereby enhances the feasibility of circuit prototyping with conductive ink.